Combining 3D printing technology with customized metal plates for the treatment of long segment femoral shaft comminuted fractures - Xu, Rongda; Liang, Yingying; Liu, Hanfei; Li, Jiahui; Zhou, Xueting; Sun, Ming; Tu, Hongliang; Zhang, Zelin; Duan, Siyu; Cai, Zhencun (Frontiers in Surgery, 2026)
ObjectiveThis study aims to evaluate the clinical value of combining 3D printing technology with customized metal plates in the treatment of long-segment femoral shaft comminuted fractures.MethodsA retrospective study was conducted on 36 patients with long-segment femoral shaft comminuted fractures who were treated at our hospital between September 2020 and September 2023. Patients were divided into two groups: the conventional group (18 patients), treated with limited open reduction and intramedullary nailing, and the 3D printing group (18 patients), which utilized 3D-printed models and customized metal plates for assisted internal fixation. Intraoperative evaluation metrics included surgical time, number of fluoroscopy exposures, and intraoperative blood loss. Postoperative evaluation metrics included the time to weight-bearing initiation, time to full weight-bearing, and fracture healing time. At 3 months post-operation and at the final follow-up, evaluations were conducted on the knee flexion-extension range of motion (ROM), hospital for special surgery (HSS) score, hip flexion-extension ROM, Harris score, visual analogue scale (VAS) score, and the occurrence of complications. At the final follow-up, lateral displacement, angular deformity, shortening deformity, and the modified radiographic union score for tibia (mRUST) score of the fracture site were evaluated.ResultsThe 3D printing group had significantly shorter surgical time and fewer fluoroscopy exposures (both P < 0.001), while intraoperative blood loss was higher but not statistically significant (P = 0.252). The 3D printing group also showed faster initiation of partial weight-bearing, full weight-bearing, and fracture healing (P < 0.001, P < 0.001, P = 0.009). At 3 months and final follow-up, the 3D printing group showed significantly better knee flexion-extension ROM, HSS score, hip flexion-extension ROM, and Harris score than the conventional group (all P < 0.001), while VAS scores showed no significant difference (all P > 0.05). At the final follow-up, the 3D printing group demonstrated better results in terms of lateral displacement, angulation deformity, shortening deformity, and mRUST score (all P < 0.001).ConclusionCombining 3D printing technology with customized metal plates in treating long-segment femoral shaft comminuted fractures improves surgical efficiency, fracture reduction and healing quality, and promotes functional recovery.